ENTERPRISE ARCHITECTURE PATTERNS WITH PYTHON : how to apply ddd, ports and adapters, and ... enterprise architecture design patterns in a pytho. - PERCIVAL, HARRY (O'REILLY MEDIA, 2020)
As Python continues to grow in popularity, projects are becoming larger and more complex. Many Python developers are now taking an interest in high-level software architecture patterns such as hexagonal/clean architecture, event-driven architecture, and strategic patterns prescribed by domain-driven design (DDD). But translating those patterns into Python isn't always straightforward. With this practical guide, Harry Percival and Bob Gregory from MADE.com introduce proven architectural design patterns to help Python developers manage application complexity. Each pattern is illustrated with concrete examples in idiomatic Python that explain how to avoid some of the unnecessary verbosity of Java and C# syntax. You'll learn how to implement each of these patterns in a Pythonic way. Architectural design patterns include: Dependency inversion, and its links to ports and adapters (hexagonal/clean architecture) Domain-driven design's distinction between entities, value objects, and aggregates Repository and Unit of Work patterns for persistent storage Events, commands, and the message bus Command Query Responsibility Segregation (CQRS) Event-driven architecture and reactive microservices.